An empirical analysis of transport and land-use integration: The case of public transport and apartment housing in Melbourne, Australia - Chris De Gruyter; Steve Pemberton; Eric Keys; Jago Dodson; John L. Renne (Journal of Transport and Land Use, 2025)
Despite widespread policy aspirations for integrating high-density housing with public transport, what is achieved in practice is rarely measured. Furthermore, equity in public transport service provision has been given little attention in areas of high-density housing. Using Melbourne as a case study, this research tracks the development of apartment housing against public transport service provision over a 19-year period. Results show that population growth (32%) outstripped modest changes in the number of public transport services provided (5%) in the areas around new apartments, with considerable growth in apartment housing occurring (88%). However, when accounting for the introduction of larger public transport vehicles in the fleet, growth in capacity-adjusted services (35%) was found to slightly exceed population growth at a metropolitan level. Yet at a local level, considerable inequity was found in the number of capacity-adjusted services provided per person across areas and routes. Evidence was also found that apartment development has been strongly attracted to areas already well served by public transport, but with little response in terms of additional services. In the case of Melbourne, it appears that the policy intent of integrating high-density housing with public transport is a one-way mechanism only.